INVENTARISASI JENIS-JENIS LUMUT DI KAWASAN HUTAN ADAT BUKIT BENUAH KABUPATEN KUBU RAYA - Putri, Shela Erika; Prayogo, Hari; Wulandari, Reine Suci (JURNAL HUTAN LESTARI, 2019)
Moss is a group of small plants that grow attached to various types of substrate, moss life is influenced by environmental factors such as temperature, humidity and light. This study aims to obtain data on the types of moss and climatic conditions in the Bukit Benuah Sungai Ambawang Customary Forest area of Kubu Raya Regency which is located in the Bukit Benuah Sungai Ambawang Customary Forest area of Kubu Raya Regency. This research was conducted for 3 months. The research uses the roaming or exploration method, which is exploring and observing the area of the research location with the number of plots as many as 3 observation plots. Sampling and collection using the touch point method in getting the types that have been sampled. There were 7 species of lichens, Brachymenium indicum, Dicranella sp, Sphagnum sp, Jungermannia sp, Monoclea forsteri, Lepraria incana, and Parmelia sp. There are 3 types of moss plants that dominate, namely Brachymenium indicum and Sphagnum sp from leaf moss and Jungermannia sp from liverworts. Environmental conditions that support the growth of moss in the Benuah Hill customary forest area are at a temperature of 21 Â° - 23 Â° C, the intensity of the incoming light is 52% - 206% and the humidity level is 78% - 83%.Keyword : Inventory, Moss, Benuah Hill